ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK PERATAAN LABA (INCOME SMOOTHING) PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Grahavor B51109070, Anton Meirio (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2013)
This study wanted to test whether the profitability, financial leverage and size of the company influence the practice of income smoothing, a company that will be sampled is a company engaged in property and real estate listing on the Indonesia Stock Exchange (BEI) in the period 2008-2011. By using purposive judgment sampling acquired 18 companies that meet the criteria to be used as the study sample. To classify the company as group grading profit or not it is used that requires Eckel index if your CV S > CV I, the company is deemed to have made ??a practice of income smoothing. With Eckel index gained 11 companies categorized as grading company earnings instead of grading and other income 7. Research results are obtained simultaneously pasrial and that profitability, financial risk and firm size has no effect on income smoothing practices (income smoothing). In other words, these three variables can not be an indicator of the company's main income smoothing practices. Keywords: Profitability, Financial Leverage, Size of the Company, Eckel Index, Income Smoothing.